Collaborative care for comorbid depression and diabetes: a systematic review and meta-analysis. Issue 4 (12th April 2014) - Atlantis, Evan; Fahey, Paul; Foster, Jann
Abstract : Objective: The collaborative care model is recommended for depression in adults with a chronic physical health problem like diabetes. We sought to systematically assess the effect of collaborative care on depression and glycaemia in adults with comorbid depression and diabetes to inform guidelines and practice. Design: Systematic review and meta-analysis. Data sources: We searched PubMed, Scopus, Cochrane Library, CINAHL, Health Source Nursing, MEDLINE, PsychINFO and reference lists of retrieved articles published before August 2013. Inclusion criteria: Randomised controlled trials (RCTs) on collaborative care (ie, coordinated multidisciplinary model of care) for depression that reported the effects on depression and glycaemic outcomes in adults with comorbid clinically relevant depression and diabetes were eligible. Data extraction and analysis: Data on the mean difference in depression and glycaemic outcomes were extracted and pooled using random effects meta-analysis. Results: Seven RCTs included for review reported effects on depression outcomes in 1895 participants, and glycated haemoglobin (HbA1c) level in 1556 participants. Collaborative care significantly improved the depression score (standardised mean difference was −0.32 (95% CI −0.53 to −0.11); I 2 =79%) and HbA1c level (weighted mean difference was −0.33% (95% CI −0.66% to −0.00%); I 2 =72.9%) compared with control conditions. Depression remission did not predict better glycaemic control across studies. Conclusions: Limited evidence from short-to-medium term RCTs predominantly conducted in the USA suggests that collaborative care for depression significantly improves both depression and glycaemia outcomes, independently, in people with comorbid depression and diabetes.